Political autobiography as objectification of an/other: A study of Mahathir Mohamad’s a doctor in the house, M.K Gandhi’sthe story of my experiments with truth, and Nelson Mandela’s long walk to freedom / Mustapha Bala Ruma - Mustapha, Bala Ruma (2017)
This thesis examines how autobiography and its variants such as the memoir transforms from being the story of the writing-‘I’ to that of its other. In this regard, the thesis specifically looks at how the texts under study turn their narratives into a process of objectification of the non-self “other” by framing their narratives through the trajectory of overarching social hierarchies such as us/them, clean/dirty, native/stranger, visible/invisible, peaceful/violent, etc. This strategy enables the writers to turn the autobiographical act into a space for accentuating differences between themselves and others. Consequently, they turn the non-self into an object and subject of difference through ridicule, disdain, mockery, and demonisation. The main aim of this strategy is to objectify the non-self by ascribing some negative qualities to it. It is the contention of this thesis that objectification as it occurs in these texts is in the main a process of identity formation based on the taxonomy of difference in the social world of the author-narrators shaped by their beliefs and ideologies. The thesis concludes that in Mahathir’s, Mandela’s, and Gandhi’s texts the “other” is used as a narrative device to construct and project a chosen and preferred positive identity of the self. In this sense, the “other” becomes a trope for self-articulation and enunciation within the textual-world of each of these writers. Viewed in this way, the “other” becomes the surface created and sustained by autobiography which could be viewed as a discourse of power on which to bounce off the contrasted image of the self.